2017
DOI: 10.1164/rccm.201703-0501oc
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm Atrophy and Weakness in the Absence of Mitochondrial Dysfunction in the Critically Ill

Abstract: Critically ill patients have manifest diaphragm muscle fiber atrophy and weakness in the absence of mitochondrial dysfunction and oxidative stress. Thus, mitochondrial dysfunction and oxidative stress do not play a causative role in the development of atrophy and contractile weakness of the diaphragm in critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
44
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 57 publications
9
44
1
Order By: Relevance
“…Diaphragmatic weakness of 15-20% as reported for heart failure in the present study is comparable with other diseases like mechanical ventilation and sepsis, 45,46 critically ill patients, 47 or pulmonary hypertension 48 and is reported to be of clinical relevance with respect to mortality. 49 In the present study, we tested the effects of compound ID#704946 when fed to animals 7 days after the MI for 9 weeks as a secondary prevention.…”
Section: Treatment Of Diaphragm Dysfunction and Atrophy By Compound Isupporting
confidence: 85%
“…Diaphragmatic weakness of 15-20% as reported for heart failure in the present study is comparable with other diseases like mechanical ventilation and sepsis, 45,46 critically ill patients, 47 or pulmonary hypertension 48 and is reported to be of clinical relevance with respect to mortality. 49 In the present study, we tested the effects of compound ID#704946 when fed to animals 7 days after the MI for 9 weeks as a secondary prevention.…”
Section: Treatment Of Diaphragm Dysfunction and Atrophy By Compound Isupporting
confidence: 85%
“… 104 More recently, the same group revealed that mitochondrial alterations and oxidative stress did not play a causative role in the development of diaphragm atrophy and contractile dysfunction in these patients. 105 It remains to be investigated whether SARS-CoV-2 patients present different cellular modifications and whether a direct attack of the virus on the muscle could be possible.…”
Section: Disorders Of Control Of Breathing and The Neuromuscular Breamentioning
confidence: 99%
“…Mitochondrion is critical in energy metabolism and playing key roles in biochemical synthesis, redox control and apoptosis. Alterations in mitochondrial function are increasingly being recognized as a contributing factor in many human diseases [ 36 39 ]. Recent understanding showed mitochondrion dysfunction and oxidative stress are usually co-existing in toxicant induced cell toxicity, and maybe a prevention method in cell toxicity [ 40 ].…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%